PERLINDUNGAN HUKUM TERHADAP NASABAH BANK SYARIAH DALAM KASUS PEMBIAYAAN BERMASALAH: STUDI KASUS DI BIREUEN - Junaidi; Muhammad Yusuf Yahya; Trina Dara Mulia; Muhammad Syazarwani (Indonesian Journal of Islamic and Social Science, 2026)
This study examines legal protection for customers of Islamic banks in cases of problematic financing, with a specific focus on Bireuen District. The background of this research arises from the increasing practice of Islamic financing that does not always proceed according to the agreed contract, thereby creating disputes between banks and customers. The objective is to analyze the forms of legal protection provided to customers, both through internal mechanisms within Islamic banks and through the Religious Courts as the competent authority in resolving disputes related to Islamic law. The research employs a qualitative descriptive approach, with data collected through literature review, interviews, and analysis of relevant legal documents. The findings reveal that legal protection for Islamic bank customers in Bireuen is carried out through two main pathways: first, internal settlement via financing restructuring, rescheduling, or re-arrangement of obligations; second, external settlement through litigation in the Religious Courts, which hold special jurisdiction over Islamic banking disputes. Furthermore, the historical and sociological context of Bireuen’s religious society strengthens the legitimacy of Islamic law in banking practices. The conclusion emphasizes that legal protection for Islamic bank customers is not only oriented toward legal certainty but also toward justice and public benefit, in line with both Islamic values and constitutional principles. Thus, the position of Islamic law in the context of Islamic banking in Indonesia, particularly in Bireuen, is an integral part of the national legal system that adapts to societal needs.